Synthesis and spectral investigations of 2,5,7-triaryl-5H-[1,3,4]thiadiazolo[3,2-?]pyrimidin-6[7H]-ones - Koparir, M; Cansiz, A; Çetin, A (Mrs Pushpa Agarwal, 2005)
A general and convenient route for the synthesis of 5-(aryl)-[1,3,4]thiadiazol-2-ylainines (2a-d), Schiff bases of thiadiazoles (3a-p) and 2,5,7-triaryl-5H-[1,3,4]thiadiazolo[3,2-a]pyrimidin-6[7H]-one (4a-p) is reported. The characterizations of these compounds were obtained by elemental analyses, IR, C-13 and H-1 NMR techniques.
Keywords: synthesis; spectral; 2,5,7-triaryl-5H-[1,3,4]-thiadiazolo[3,2-alpha]pyrimidin-6[7H]-ones